Personality Traits and Body Weight Measures: Concurrent and Across–Time Associations†. Issue 4 (July 2013) - Armon, Galit; Melamed, Samuel; Shirom, Arie; Shapira, Itzhak; Berliner, Shlomo
We tested the possibility that the five–factor model of personality is associated with three measures of body weight and with changes in their levels over time and that these associations are gender specific. The study was conducted at two points of time, Time 1 (2664 participants) and Time 2 (1492 participants), over approximately 4 years, controlling for gender, age, education, and having a chronic disease. Body weight was assessed by body mass index, waist circumference, waist–to–hip ratio, and the five–factor model by Saucier's Mini–Markers. Cross–sectional regression results indicated that conscientiousness was negatively associated with the three body weight measures, whereas neuroticism and extraversion were positively associated with the three body weight measures. The longitudinal regression results indicate that extraversion was associated with an increase in two of the body weight measures. Neuroticism was associated with increase in all three body weight measures and more strongly for women than for men. Openness was associated with a decrease in all three body weight measures for women, but this association was not significant for men. These findings help identify personality traits that lead to risk of weight gain and point to the modifying role of gender. Copyright © 2013 John Wiley & Sons, Ltd.